Editorial - Judith Winters (Internet Archaeology, 2003)
The first article to be published in this issue was a research article by Symonds and Ling on concepts of time and travel in early medieval England. The authors focus on the production and consumption of artefacts, specifically pottery, in Anglo-Scandinavian Lincolnshire and used approximations of distance based on road and river routes, as well as the estimations of the time it took to travel along those routes during the early medieval period, to analyse the pottery distribution in Lincolnshire. An interesting element of the publication was the inclusion of a 'Java' map interface designed by the authors which mimics the interactive abilities of a GIS and allows readers to investigate the patterns of data for themselves.